ANALISIS POSTUR PEKERJA PRODUKSI MAGGOT PADA STASIUN KERJA BIOKONVERSI PT. ABC - Firdausi, Wafa Al; Arsiwi, Pramudi (Nusantara Hasana Journal, 2025)
One of the work stations at PT. ABC is the Bioconversion work station (maggot enlargement). At this work station out were approximately 10 minutes for each biopond tank in 1 working day, with a total of 21 tanks. Workers often experience fatigue, especially in the back and neck areas. Therefore, an analysis was carried out on the fatigue factors experienced by workers. In this study, the method used to analyze worker posture is Rapid Entire Body Assessment (REBA). The REBA method is used to analyze overall body posture, and then the results will be tested using Ergofellow software. The results obtained from the investigation of worker posture at the bioconversion work station using Ergofellow software got a score of 6, with a moderate risk. This is because the biopond design is less than ideal. So, the proposed improvement given is to redesign the biopond design, with the hope that workers will no longer bend over when doing work and can minimize the risk of injury.